The role of specific physical activitiesin archive work - Leuciuc Roxana Melania (Editura Univeristatii "Stefan cel Mare" din Suceava, 2022)
The effects of physical activity are beneficial on the physical condition which aims to obtain a very good physical shape, as well as motor, functional and mental benefits. This article aims to draw attention to the fact that, despite the technology development, the electronic archiving law, the activity that the archivist carries out, for most of the work schedule, involves physical activity. Archivists must not only be professionals in the field of archiving, but they also must juggle records in archives, so that their health is not affected. Performing constant exercises inside the office and in free time / leisure will contribute to the physical condition development, have positive effects both personally and professionally, bringing benefits in order to carry out the daily activities with the highest efficiency.